Accounting for Musical Perception Through Equivalence Relations and Abstraction: An Experimental Approach - Luis Fernando Toniollo Reis (International Journal of Psychology and Psychological Therapy, 2017)
The present study aimed to establish equivalence classes between musical chords, the corresponding chord grids, and the labels for each chord type (major, minor and 7th). Seven adults participated in a computerized matching-to-sample procedure. During training sessions, participants learned relations between chords of the same root note and either their corresponding chord grids or the words labeling their type. Equivalence relations between grids and words were then veriÀed, and a generalization test assessed abstraction of the chord type with previously untrained chords. Phase 1 used chords having C as the root note. Phases 2 and 3 were programmed similarly, using chords having E and G as their root notes. Most participants had positive results on equivalence tests. Across the experimental phases, the percentage of correct choices in the generalization tests increased gradually for four out of seven participants. A behavioral account of musical perception through the concept of abstraction is discussed.